O lugar do brincar no espaço da educação infantil: narrativas de educadoras da rede pública municipal de São Luís - MA - MACHADO, Magali Dias da Conceição (2023)
This research was developed in the Postgraduate Program in Basic Education Teaching Management (PPGEEB) at the Federal University of Maranhão and its main objective was to investigate the relationships and meanings of play that remain in teaching practice in the voices of pre-school educators. school of a municipal basic education unit in São Luís-MA with the aim of building an educational product. In methodological terms, the research was characterized as exploratory, articulating bibliographical research and collaborative research. The main bibliographical references, considering play and teacher training as a research basis, were: Vigotski (2008), Proença (2018), Friedmann (2012), Wajskop (2011), Fortuna (2018) and Kishimoto (2010) and having 7(seven) preschool educators participated. The survey, systematization and data analysis included the assumptions of the comprehensive interview expanded by observations and reflective play sessions, enabling an approach to the meanings given to playing. As a result, we realized that playing is strongly associated with childhood and children, however, it still remains at a certain distance and insecurity from an everyday and fundamental activity for childhood school. During the investigation, we noticed that educators recognize the importance of playing not only through theoretical studies, but above all through their experiences during childhood. The data present the need to review the training processes through playful teacher training with the intention of rescuing playing so that it begins to occupy all spaces of Early Childhood Education without resistance or insecurity. We hope that this research will help other educators to reconnect with their inner child in order to ensure full play in Early Childhood Education spaces.